Man on horseback - "Finer, S.E." (Boulder, 1988)
This book contains following topics: The military in the politics of Today; The ,political Strengths of the Military; The political Weaknesses of the Military; The Disposition to Intervene; The opportunity to Intervene; The levels of intervention; The modes of Intervention etc.
Keywords: Civil Military relations